Recyclable Cytokines: Recyclable Cytokines on Short and Injectable Polylactic Acid Fibers for Enhancing T‐Cell Function (Adv. Funct. Mater. 14/2019). (1st April 2019) - Shin, Hyun Mu; Ju, Youngjun; Kim, Gwanghun; Lee, Jae Won; Seo, Myung Won; Sim, Ji Hyun; Yang, Jusang; Noh, Sora; Kim, Jungbae; Kim, Hang‐Rae
Abstract : In article number1808361, Jungbae Kim, Hang‐Rae Kim, and co‐workers inject cytokine‐immobilized short polylactic acid (PLA) fibers (Cyto‐sPLA) near a tumor to reinvigorate nonfunctional T cells. The administration of Cyto‐sPLA fibers kills tumor cells and ultimately effectively inhibits tumor growth. Injectable Cyto‐sPLA fibers have great potential for the development of anticancer therapeutics.